Multivariate Analysis of the Historical Precipitation of Nicaragua, Costa Rica, and Honduras with the Global Historical Precipitation from WorldClim. (Global Journal of Science Frontier Research, 2023)
The present investigation includes the analysis of the correlation of the variable historical precipitation of the Nicaraguan airport station the El Indio coffee plantation station San Vito-Puntarenas in Costa Rica and the Amapala station in Honduras versus the historical precipitation of global data from WorldClim based on of the multivariate correlation analysis technique The research questions are formulated in relation to the correlation of historical precipitation data at three different points in the Central American region versus the WorldClim global precipitation database and that these can be used to perform specific hydrological analyzes at lack of them As a result four possible combinations were produced where Y were the global WorldClim data the data from the Nicaragua station then the data from the Costa Rica station and finally the data from the Honduras station determining R2 correlations of the order of 0 98 0 98 0 99 and 0 95 respectively this goodness-of-fit correlation indicates that there is a lot of precision demonstrating that the data from WorldClim or from another station in the Central American region can be used from the calculated coefficients to perform hydrological studies in the absence of information
Keywords: worldclim; correlation analysis; multivariate; precipitation; hydrology